Analysis and design of cable-driven parallel kinematic mechanisms - Pham, Cong Bang (2008)
This thesis concerns the analysis and design of cable-driven parallel mechanisms (CDPM). Structurally, a CDPM is formed by replacing the supporting legs of a parallel mechanism with active cables. It has the advantages of simple mechanical structure, low moment of inertia, and high-speed motion. One distinctive characteristic of CDPMs is the unilateral property of the cables, i.e. cables can only pull but not push. At present, the design and application of CDPMs are limited and there is a lack of systematic analysis methods for CDPMs. This work aims to lay down a framework for the analysis, design and application of fully restrained CDPMs.